A Systematic Review and Meta-Analysis of the Use of the National Institutes of Health Toolbox Cognition Battery in Clinical Populations - Kelly H. Watson; Abagail E. Ciriegio; Claire F. Miller; Marissa C. Roth; Bruce E. Compas (Neuropsychology Review, 2026)
The National Institutes of Health Toolbox Cognition Battery (NIHTB-CB) is an assessment tool that has been widely utilized in research with clinical populations across the lifespan. Despite its widespread use, a systematic review and meta-analysis of cognitive function utilizing this battery in clinical samples has not been reported. To address this gap, 84 studies were identified after systematically searching PsycINFO, PubMed, and ProQuest (71 peer-reviewed articles, 11 dissertations, 2 master’s theses) comprising 6331 clinical participants. Study quality was assessed using the QUADAS-2 tool. Results identified significant deficits in the Fluid Cognition Composite and the associated subtests (attention, working memory, processing speed, executive function) in clinical samples when compared to both the NIHTB-CB normative data and recruited comparison samples. Unexpectedly, there was some evidence that clinical participants scored higher on Crystallized Cognition subtests than the normative data but scored significantly lower than recruited controls. There was mixed evidence for performance differences on a Total Cognition Composite measure of cognitive function. There was some evidence of publication bias, and results were moderated by study quality and participant demographics. The implications of the findings for clinical research settings are discussed and suggested future directions are provided.